2022
DOI: 10.3390/molecules27113394
|View full text |Cite
|
Sign up to set email alerts
|

Structural Investigation of the Interaction Mechanism between Chlorogenic Acid and AMPA Receptor via In Silico Approaches

Abstract: Chlorogenic acid (CGA), an important metabolite in natural plant medicines such as honeysuckle and eucommia, has been shown to have potent antinociceptive effects. Nevertheless, the mechanism by which CGA relieves chronic pain remains unclear. α-amino-3-hydroxy-5-methyl-4-isooxazolpropionic acid receptor (AMPAR) is a major ionotropic glutamate receptor that mediates rapid excitatory synaptic transmission and its glutamate ionotropic receptor AMPA type subunit 1 (GluA1) plays a key role in nociceptive transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…They demonstrated a significant reduction of thermal, but not mechanical hyperalgesia and discovered that the compound interacts with the serotonin system, inhibits MAO-A activity, and activates 5-HT7 receptors at the spinal but not at the supraspinal level. They also confirmed fisetin (60) antihyperalgesic action (15-45 mg/kg) on thermal hyperalgesia and mechanical allodynia in diabetic neuropathic pain model, by its antioxidant activity in dorsal root ganglia and spinal cord of mice, but not supraspinal GABAA receptor involvement.…”
Section: Fisetinsupporting
confidence: 59%
See 3 more Smart Citations
“…They demonstrated a significant reduction of thermal, but not mechanical hyperalgesia and discovered that the compound interacts with the serotonin system, inhibits MAO-A activity, and activates 5-HT7 receptors at the spinal but not at the supraspinal level. They also confirmed fisetin (60) antihyperalgesic action (15-45 mg/kg) on thermal hyperalgesia and mechanical allodynia in diabetic neuropathic pain model, by its antioxidant activity in dorsal root ganglia and spinal cord of mice, but not supraspinal GABAA receptor involvement.…”
Section: Fisetinsupporting
confidence: 59%
“…hupehana (Craib) T.C.Chen, fisetin (3,3′,4′,7-tetrahydroxyflavone) (60, Figure 34), a flavonoid compound able to overcome the BBB, is one of the most studied for its analgesic, antidepressant, and neuroprotective action. It was deeply investigated fisetin (60) analgesic action in the CCI model (15 and 45 mg/kg administered p.o. twice a day for 3 weeks) [43].…”
Section: Fisetinmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have indicated that Lonicera japonica extracts and functional components found in Lonicera japonica extracts, such as flavonoids, phenolic acids, and polysaccharides, could treat many conditions. They included inflammatory diseases [22] , vascular senescence [23] , diabetes, obesity [24] , hyperuricemia [25][26] , and pain [27][28] , atherosclerosis, chronic obstructive pulmonary disease, idiopathic pulmonary fibrosis, hypertension [29] , Alzheimer's disease, cancer [30][31] , etc. Before discussing the health effects of Lonicera japonica against these diseases, the pathogenesis of the diseases should be reviewed, so that we can better understand how the functional components of Lonicera japonica play a role in preventing the occurrence and development of the diseases.…”
Section: Health Effects and Mechanisms Of Action Of Lonicera Japonicamentioning
confidence: 99%